Medication Class Effects on Visit‐to‐Visit Variability of Blood Pressure Measurements: Analysis of Electronic Health Record Data in the "Real World". Issue 9 (12th July 2013) - Smith, Timothy R.; Drozda, Joseph P.; Vanslette, Jeffrey A.; Hoeffken, Amanda S.; Nicholson, Robert A.
Abstract : Blood pressure (BP) visit‐to‐visit variability (VVV) influences the risk of vascular events and mortality. Research has suggested that antihypertensive medication classes may differentially impact VVV. This study evaluated whether antihypertensive medication class differentially impacted BP VVV among hypertensive individuals in a clinical, "real‐world" setting as well as the association between VVV and patient characteristics. Clinical observational data were extracted for adults (mean age, 63; 56% female, 86% Caucasian) with hypertension from the Mercy EpicCare EHR‐Derived Database (MEDD) (n=183, 374) who had at least 4 outpatient visits with BP readings. A multilevel mixed model for change over time estimated between‐ and within‐subject effects on the absolute real VVV of systolic BP. Diuretics significantly lowered VVV (β=−0.32[−0.39 to−0.25]) and α‐/β‐blockers resulted in the highest VVV (β=0.89 [0.77–1.00]). Being older, female, and having a higher systolic BP and certain comorbid conditions significantly raised VVV ( P <.001). The findings from the MEDD were consistent in general with other research on BP VVV. However, the magnitude of effect of antihypertensive medication class and patient characteristics was relatively low (<10% of the BP VVV variance for any one variable). More research is needed to evaluate the extent to which the class of antihypertensive medication class impacts BP VVV in the outpatient setting.